Морфо-синтаксическая структура коммуникативных ситуаций каузации радости (на материале польского языка) - Zakusylo, Daryna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The article analyses the morphological and syntactic expression of the causator (or cause) in the communicative situations of causation of joy in the Polish language. By causation we mean the semantic category which expresses the causal relationships between the fundamentals of non-linguistic reality. The purpose of this study is to analyse the syntactic structure of communicative situations of causation of joy, on the semantic level of which there are such actants as: agent, experiencer, causator (or cause). All of the analysed constructions were divided into three groups: agentive split constructions, agentive unsplit constructions and non-agentive constructions. Split constructions refer to those in which the agent and causator are separate actants, while unsplit ones refer to those in which these semantic roles are combined into one actant. The results of the study show that the most numerous group among the examples is that of non-agentive constructions.